Characteristics of computed tomography in hemodynamically unstable blunt trauma patients: Experience at a tertiary care center. Issue 49 (December 2017) - Kim, Youn-Jung; Kim, June-Sung; Cho, Soo-Han; Bae, Jun-Il; Sohn, Chang Hwan; Lee, Yoon-Seon; Lee, Jae-Ho; Lim, Kyoung-Soo; Kim, Won Young
Abstract : Abstract: Emergent exploratory laparotomy is recommended for hemodynamically unstable blunt trauma patients suspected of having hemoperitoneum. However, given the unreliability of ultrasonography and rapid scan speed of computed tomography (CT), CT might help clinicians provide accurate information even in hemodynamically unstable trauma patients. This observational study aimed to describe the bleeding site and hospital course of severe blunt trauma patients with hemoperitoneum diagnosed by CT scan. We enrolled all consecutive adult blunt trauma patients (≥18 years old) who underwent whole-body CT before operation between February 2012 and October 2016. Patients with hemoperitoneum on CT images were included and categorized into hemodynamically stable and unstable (persistent hypotension despite fluid resuscitation) groups. Among 1723 severe blunt trauma patients, 136 patients with hemoperitoneum were included. Of these, 98 (72.1%) patients had documented intraperitoneal injury, and the liver (60.2%) was most frequently damaged site, followed by spleen (23.5%) and mesentery (23.5%). The rate of intraperitoneal organ injury did not differ between hemodynamically stable (n = 107) and unstable (n = 29) groups (69.2% vs 82.8%, P  = .15), while the documented active internal bleeding was high in the unstable group (29.9% vs 69.0%, P  < .001). In the unstable group, 14 (48.3%) patients underwent emergent operation, while 3 patients underwent embolization, and the others were treated in a conservative manner. Even in hemodynamically unstable hemoperitoneum patients, 17.2% had no documented intraperitoneal injury and over half of the patients were treated without emergent operation.